Refractive errors among children attending a tertiary eye facility in Ibadan, Nigeria: highlighting the need for school eye health programs (2019)
Background: It is estimated that 19 million children aged below 15 years are visually impaired globally. Twelve million of these are due to uncorrected refractive errors. The aim of this study was to describe the pattern of refractive errors seen in children attending the eye clinic of the University College Hospital, Ibadan, Nigeria. Methods: A descriptive retrospective study of children with refractive errors seen between January 2011 and December 2012 was conducted. Information on the age, sex, type of refractive error, degree of error (spherical equivalent), presenting complaint, previous spectacle use and return for follow-up visit were retrieved and analyzed using SPSS version 20. Results: Three hundred and sixty-six children diagnosed with refractive errors accounted for 34.6% of all children seen. Of these, 267 (73%) records were successfully retrieved. The mean age was 10.58 (± 3.14) years, with 156 (58.5%) aged between 11 and 15 years. The male to female ratio was 1:2. The commonest refractive error was myopia, found in 124 (23.2%) of 534 eyes followed by simple myopic astigmatism and compound myopic astigmatism found in 117 (21.9%) and 111 (20.8%) eyes respectively. Majority, 229 (85.8%) had never worn spectacles previously and only 80(30%) children returned for a follow up visit. Conclusion: Refractive errors constitute a common diagnosis among children seen in our tertiary eye facility. Late presentation and poor follow up among our patients are a cause for concern. Public enlightenment, health education and school eye programs are recommended to reverse this trend.